BIOMASS AND DENSITY OF SEAGRASS Enhalus acoroides IN THE VILLAGE WATERS JAGO-JAGO OF TAPANULI TENGAH NORTH SUMATERA PROVINCE - Emilia Azizah; Syafruddin Nasution; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research has been conducted in the month of February – April 2017 at Village Waters Jago-Jago of Tapanuli Tengah North Sumatera. The aim of this study was to determine the density and biomass and station characteristics determine the effect of the density and biomass of seagrass Enhalus acoroides in Village Waters Jago-Jago North Sumatera. Results showed the highest density of seagrass Enhalus acoroides was located on the mangrove forest community areas (station III) in the amount of 45,55 shoots/m2. Enhalus acorides biomass was highest at station III with a dry weight of 110,70 gr/m2. The lowest of seagrass biomass was at residential areas (station I) with a dry weight of 75,5 gr/m2. The result of simple linier regression test for the effect of density on biomass obtained r = 0,717.Keywords : Enhalus acoroides, Density, Biomass, Village Waters Jago-Jago